2014
DOI: 10.1186/1756-3305-7-119
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of tick-transmitted pathogens in dogs in Jos, Plateau State, Nigeria

Abstract: BackgroundCanine babesiosis caused by Babesia rossi, transmitted by Haemaphysalis elliptica in South Africa, has also been reported from Nigeria. Although H. leachi (sensu lato) is widespread in sub-Saharan Africa, published literature on the occurrence of canine babesiosis is meagre. It has been postulated that the genotype of Babesia rossi Erythrocyte Membrane Antigen 1 (BrEMA1) may be linked to virulence of the specific isolate. The primary objective of this study was to detect and characterise tick-borne p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 44 publications
4
59
2
Order By: Relevance
“…This is lower than the prevalence of 38.5% reported by Okubanjo et al, (2013) in Sokoto using microscopy also and this might be due to different geographical locations where the studies were carried out and the type of dogs that were sampled. The prevalence in this study is also much lower than 54% reported by Adamu et al, (2014) in Jos, Nigeria. This is not unexpected as Adamu et al used serology which is known to detect both active and passive infections unlike microscopy which tend to detect only active parasites circulating in the system as at when sampled.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This is lower than the prevalence of 38.5% reported by Okubanjo et al, (2013) in Sokoto using microscopy also and this might be due to different geographical locations where the studies were carried out and the type of dogs that were sampled. The prevalence in this study is also much lower than 54% reported by Adamu et al, (2014) in Jos, Nigeria. This is not unexpected as Adamu et al used serology which is known to detect both active and passive infections unlike microscopy which tend to detect only active parasites circulating in the system as at when sampled.…”
Section: Discussioncontrasting
confidence: 70%
“…This stimulated renewed interest in the epidemiology of canine babesiosis in Africa, as it was the first confirmation of the occurrence of Babesia canis in a geographical region were Dermacentor reticulatus, the only confirmed vector of Babesia canis, does not occur (Kamani et al, 2010). According to Adamu et al, (2014) the prevalence for Babesia rossi was 13% and Babesia vogeli 1% out of one hundred samples analyzed using the Reverse Line Blot (RLB) assay. To the best of our knowledge and as at the time of this write up, there are no available publications on the prevalence of Babesia species in hunting dogs in Nigeria who are at the interface of transmission cycle having gone to the wild for hunting and are brought back to the sentinel of their owners in the owners' abode with the attached arthropods that are vectors of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We extracted DNA from whole blood (QIAamp DNA mini kit, Qiagen, Whitehead Scientific, South Africa) and tested for Anaplasma-Ehrlichia and Babesia-Theileria by amplification of the 16S and 18S rRNA genes, respectively, and reverse line blot hybridization (RLBH) assay with genuswide and species-specific probes (Adamu et al 2014). For two lions positive with only the Babesia genus-wide probe, near full-length 18S rRNA gene was amplified, gel purified, and sequenced by Inqaba Biotec (Pretoria, South Africa) as described by Adamu et al (2014).…”
Section: Serologic and Microbiologic Diagnostic Testingmentioning
confidence: 99%
“…For two lions positive with only the Babesia genus-wide probe, near full-length 18S rRNA gene was amplified, gel purified, and sequenced by Inqaba Biotec (Pretoria, South Africa) as described by Adamu et al (2014). For two additional lions that were positive with more than one species-specific probe, the 18S rRNA gene was amplified and purified DNA was ligated into the pGEM-T Easy Vector and transformed into JM109 High Efficiency Competent cells (Promega, Madison, Wisconsin, USA).…”
Section: Serologic and Microbiologic Diagnostic Testingmentioning
confidence: 99%
“…In southern Europe the disease is caused by Babesia canis for which the ornate dog tick (also known as the meadow tick) Dermacentor reticulatus (previously known, among other names, as D. reticularis) is the vector. It too transmits the B. rossi parasite (Uilenberg et al 1989;Adamu et al 2014). Though B. vogeli also occurs there, B. rossi is restricted to Sub-Saharan parts of Africa.…”
Section: Canine Babesiosismentioning
confidence: 99%